Risk pooling, leverage, and the business cycle - Pietro Dindo; Andrea Modena; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2020)
This paper studies the impact of financial sector size and leverage on business cycles and risk-free rates dynamics. We model a general equilibrium productive economy where financial intermediaries provide costly risk mitigation to households by pooling the idiosyncratic risks of their investment activities. We find that leverage amplifies variations of intermediaries' relative size, but may also mitigate the business cycle. Moreover, it makes risk-free rates pro-cyclical. Households benefit the most when the financial sector is neither too small, thus avoiding high consumption fluctuations and costly mitigation, nor too big, so that fewer resources are lost after intermediation costs.
Keywords: E13; E32; E69; G12; 330; Business Cycle; Frictions; Leverage; Mitigation; Risk Pooling